2008
DOI: 10.1002/jcb.21899
|View full text |Cite
|
Sign up to set email alerts
|

HIP/RPL29 antagonizes VEGF and FGF2 stimulated angiogenesis by interfering with HS‐dependent responses

Abstract: HIP/RPL29 is a heparan sulfate (HS) binding protein with diverse activities including modulation of heparanase (HPSE) activity. We examined HIP/RPL29’s ability to modulate actions of HS-binding growth factors (HBGFs) in angiogenesis. Between 1–2.5 μg/ml (ca. 60–150 nM), HIP/RPL29 inhibited HBGF-stimulated endothelial cell tube formation. Aortic explant outgrowth also was inhibited, but at higher concentrations (40 μg/ml). At this concentration, HIP/RPL29 had no effect on HBGF- stimulated MAPK phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The HS dependent binding of VEGF 165 to immobilized PlnDI described herein is consistent with recent reports [5,6]. In contrast, a new communication has reported PlnDI does not bind immobilized VEGF 165 [36].…”
Section: Discussionsupporting
confidence: 92%
“…The HS dependent binding of VEGF 165 to immobilized PlnDI described herein is consistent with recent reports [5,6]. In contrast, a new communication has reported PlnDI does not bind immobilized VEGF 165 [36].…”
Section: Discussionsupporting
confidence: 92%
“…Its patterns of expression are consistent with a role in extracellular matrix remodeling as well as growth factor release. Two proteins have been identified that are naturally occurring inhibitors of heparanase activity, namely eosinophil major basic protein [68] and heparin/HS-binding protein/RPL29 [69]. In addition to inhibiting heparanase-1 activity, HIP/RPL29 also displaces HS-binding growth factors from HS-bearing substrates [69].…”
Section: Heparanases and Sulfsmentioning
confidence: 99%
“…Two proteins have been identified that are naturally occurring inhibitors of heparanase activity, namely eosinophil major basic protein [68] and heparin/HS-binding protein/RPL29 [69]. In addition to inhibiting heparanase-1 activity, HIP/RPL29 also displaces HS-binding growth factors from HS-bearing substrates [69]. Thus, a complex scenario exists where HIP/RPL29 displays seemingly antagonistic actions in terms of HS-binding growth factor release.…”
Section: Heparanases and Sulfsmentioning
confidence: 99%
“…However, in mouse cells the surface expression of RPL29 has not been demonstrated (Kirn-Safran et al, 2007) and our data corroborate this finding. At the surface of human cells, the heparin/heparan sulphate binding property of RPL29 can regulate responses to growth factors (Rohde et al, 1996; Jacobs et al, 1997; Liu et al, 1997; Rohde et al, 1998; Lander and Selleck, 2000; D’Souza et al, 2008). Indeed, application of synthetic RPL29 peptides has been shown to interfere with heparan sulphate binding to VEGF and FGF thus inhibiting angiogenesis ex vivo (D’Souza et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Rpl29 -null embryonic fibroblasts have decreased rates of proliferation and protein synthesis (Kirn-Safran et al, 2007). Although a synthetic RPL29 peptide has been shown to inhibit VEGF-and FGF-induced angiogenesis via its interaction with cell surface heparin and/or heparan sulphate proteoglycans (D’Souza et al, 2008), endogenous, cellular RPL29 has not been shown to be involved in angiogenesis.…”
Section: Introductionmentioning
confidence: 99%